Efektivitas Metode Pebelajaran Group Investigation Terhadap Prestasi Belajar Siswa - Alpi Zaidah; Alpiana Hidayatulloh (Literasi: Jurnal Pendidikan Guru Indonesia, 2022)
Study this aim for know effectiveness use method learning Group Investigations to physics science learning achievement Theory heat student Class VII MTs. Mu'allimin NW Kelayu. Learning with method Group Investigation IPA physics give chance wide to participant educate for develop knowledge in solve related issues with their lessons face. This study uses true experimental research. The population is students of class VII MTs. Mu'allimin NW Kelayu with three classes. Sampling of this research determined randomly with cluster random sampling technique. There are three groups (group study) or group study class VII in MTs. Mu'allimin NW Kelayu. However, from three groups, two classes were randomly selected, totaling 40 students. Sample taken that is student class VIIB as group control and student Class VIIA as group experiment. Class VIIA as class experiment totaling 20 students given treatment with method Group Investigation, meanwhile class VIIB as class control too a total of 20 is given treatment with method conventional (lecture). Draft research used is “ The Post-Test Only Control Design”. Data collection techniques for cognitive achievement with the test method with multiple choice types (multiple choice). Data collected with use instrument in the form of an achievement test learn. The average value of the achievement test acquired learning class taught experiment with using the cooperative learning model of the Group Investigation type is 70.25 , meanwhile the average value of the achievement test acquired learning class being taught with method conventional (lecture) is 56.75 . After test precondition so could conducted test hypothesis an analysis using the t-test, obtained information on the price of t count = 2.98 while the price of t table with dk = n 1+n 2 -2 with a significant level 5% obtained t table = 1.684. Then t count > t table . So that it can be concluded that the method learning Group Investigation is effective to achievement learn IPA physics Theory odd semester calorie student class VII MTs. Mu'allimin NW Kelayu academic year 2021/2022.